Parameters for digital neutron radiography at triga mark II research reactor of Malaysian nuclear agency - Hasham @ Hisam, Rosdiyana (2008)
Neutron radiography has been widely employed in nondestructive testing technique to detect the structural nature of internal defects of optically opaque materials. For many years, conventional neutron imaging technique has been carried out using analogue technology which uses film as means for imaging. In making transition from analogue to digital technology, several parameters have to be optimized. Beam size and neutron flux have been identified as two principal. parameters to develop digital neutron radiography. The parameters will be considered as a point to get a neutron beam to suit the scintillator size of detector and produced high quality image. Safety of the equipment was also important to protect the electronic component of the detector from damaged. In this study, a cooled charge couple device (CCD) camera system was used and a shielding is adopted to protect the CCD camera from unnecessary radiation. Therefore the thickness estimation of shielding was obtained and verified by gamma ray dose mapping. The neutron beam size has been modified by attaching a simple collimator beam plug to the neutron radiography 2 (NUR-2) beamport to accommodate 5 em x 6 ern dimension of the scintillator screen placed in the CCD camera. With the collimator beam plug attached, the neutron beam effective diameter is reduced to 7.2 em from 15.8 em which effectively covers the scintillator area. The thermal neutron flux through the collimator beam plug at CCD camera location was 2.674 x 10 5 ncm-2s-1. The neutron flux obtained is within the acceptable levels for the CCD camera requirement. Meanwhile the gamma ray dose with CCD camera shielding was less than 30 mfiyh' . The gamma ray dose mapping indicates the shielding was effective in protecting the electronic components from damaged. These experimental results consistent with the result of the analysis on the digitized the radiographic image produced using a conventional technique